Cảnh báo sớm khủng hoảng hệ thống ngân hàng Việt Nam - Hạ Thị Thiều , Dao; Nguyễn Thị Mỹ , Phượng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
By means of the banking sector fragility index, this study identifies the banking system crises occurring in Vietnam from January 2009 to May 2009, and from May 2011 to December 2015. Then, through Signal, Logit and BMA approaches, the paper points out the most effective macroeconomic indicators to give early warnings for Vietnam’s banking systemic crises, and calculates the probability chain of early warnings for systemic banking crises in Vietnam from January 2002 to December 2015. The study results show that 14 variables are highly effective for crises warning, including domestic credit-to-GDP ratio, inflation, real interest rates, real exchange rate, industrial production index, bank deposits, composite stock price index, exchange market pressure index, loans-to-deposit ratio of the banking system, export, import, M2-to-reserve ratio, M2 multiplier, and reserves.